Notes on the genus Gryllacris Audinet-Serville (Orthoptera: Gryllacrididae) with description of a new species from China - Wang, Han-Qiang; Liu, Xian-Wei (Zootaxa, 2022)
In this work we briefly reviewed the genus Gryllacris with some notes on taxonomic issues, note the taxa that have been described in and transferred to the genus and describe a new taxon, Gryllacris (Gryllacris) stylommatoprocera, from Yunnan, China. Materials are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences.